Nicanquimatizque (here it will be known) (Urdimbre y Trama, Revista Mexicana de Religiosidad Popular, 2023)
In this text we will approach to the Nahuatl indigenous source of the Mexican Songs as a comparative source for the literary environment of the Nican Mopohua, making an analogy with it. We are going to deal with explicit texts and key words that have points of contact between these two literary texts, revealing a literary context with certain conventions in language management and the transmission of sublime ideas. We will see the importance that they have to make observations of the cultural context and to have a critical eye regarding the Nahuatl historical-cultural context of the time in which the Guadalupan Event is circumscribed.
Keywords: Guadalupe; Nican Mopohua; mexican songs; flower and song; Tloque Nahuaque; Ipalnemohuani; tilma